Análise de possíveis determinantes da penetraç\~ao do serviço de acesso à Internet em banda larga nos municípios brasileiros - Hildebrando Rodrigues Macedo; Alexandre Xavier Ywata de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– In this paper, by using cross-section regression analysis, we studied the economic and human development factors affecting the diffusion of the broadband internet access at the level of municipalities in Brazil. As economic development indicators we used the GDP per capita, GDP and how it is distributed among the Agricultural, Industrial and Services sectors, for the year 2007. For the human development indicators we employed the Firjan Human Development Index for the year 2005. Broadband accesses data was provided by Anatel.
Keywords: C21; O33; 330